Damage Analyses of Replaceable Links in Eccentrically Braced Frame (EBF) Subject to Cyclic Loading - Zhanzhong Yin; Dazhe Feng; Wenwei Yang (Applied Sciences, 2019)
In the current design of steel eccentrically braced frames (EBFs), the yielding link is coupled with the floor beam. This causes the design of cross-sectional dimensions of links to be enlarged, resulting in over-designed structures and foundations, and increasing the cost of the overall structure. In addition, the beams are forecast to sustain severe damage through repeated inelastic deformations under design-level earthquakes, and thus the structure may require extensive repair or need to be replaced. To improve upon these drawbacks, a shear device with replaceable links based on EBFs was designed. The hysteresis curve, the stress distribution, and the deformation of the specimen were obtained by cyclic loading tests of the eight replaceable links. The energy dissipation behavior, the bearing capacity, the failure modes, and the plastic rotation angle of those specimens were analyzed. The results indicated clearly that the links in this shear device had inelastic deformation concentrated in the link showing very stable hysteresis behavior, and damaged links were replaced easily as end-plate connections were adopted. The energy dissipation capacity and the plastic rotation angle of the specimens were mainly dependent on the arrangement of stiffener, length ratio, and welding access holes. Experimental studies performed in this research and the related damage analyses reveal that cracks are the major causes of damage to the EBF and there is a lack of research on real-time monitoring of the onset and development of these cracks in EBF structures. As a future work, this paper proposes a piezoceramic patch transducer-based active sensing approach to monitor the crack onset and development of the EBF when subjected to dynamic loadings.